Development of a minimal medium for Clostridium perfringens by using an anaerobic chemostat. - Goldner, S B (1985)
A minimal medium was developed for the cultivation of Clostridium perfringens in an anaerobic chemostat. Cultures of C. perfringens ATCC 3624 and NCTC 10240 were grown at 46 and 43 degrees C, respectively, in a glucose-limited, chemically defined medium at pH 7.2. The concentrations of amino acids, minerals, nucleotides, and vitamins, initially present in excess, were varied independently. The minimum concentration of each nutrient which would support 3 X 10(8) CFU/ml with a generation time of less than 40 min was determined and used to develop a reformulated defined medium. Atomic absorption spectroscopy and amino acid analyses of the reformulated medium indicated additional adjustments in nutrient content which led to the development of a minimal medium for each strain. The nutritional profile for each strain was similar. A decrease in the concentration of arginine, histidine, and tyrosine for strain 3624 and of arginine, histidine, and isoleucine for strain 10240 resulted in an increase in the optical density of each culture.